Employment Protection Legislation and the Size of Firms - Pietro Garibaldi; Lia Pacelli; Andrea Borgarello (Institute for the Study of Labor (IZA), 2003)
The existing literature ignores the fact that in most European countries the strictness of Employment Protection Legislation (EPL) varies across the firm size distribution. In Italy firms are obliged to rehire an unfairly dismissed worker only if they employ more than 15 employees. Theoretically, the paper solves a baseline model of EPL with threshold effects, and shows that firms close to the threshold are characterized by an increase in inaction and by a reluctance to grow. Empirically, the paper estimates transition probability matrices on firm level employment using a longitudinal data set based on Italian Social Security (INPS) records, and finds two results. First, firms close to the 15 employees threshold experience an increase in persistence of 1.5 percent with respect to a baseline statistical model. Second, firms with 15 employees are more likely to move backward than upward. Finally, the paper tests the effect of a 1990 reform which tightened the regulation on individual dismissal only for small firms. It finds that the persistence of small firms relative to large firms increased significantly. Overall, these threshold effects are significant and robust, but quantitatively small.
Keywords: J4; 330; employment protection legislation; firm size; Arbeitsrecht; Kündigungsschutz; Betriebsgröße; Unternehmenswachstum; Schätzung; Theorie; Italien